2009
DOI: 10.1186/1471-2474-10-125
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of MRI in prediction of malignancy of musculoskeletal system-A prospective evaluation

Abstract: Background: The purpose of this study is to evaluate the role of MRI in musculoskeletal tumours, especially, in prediction of malignancy & to compare whether the diagnosis made on MRI correlates with the cytological/histopathological diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…The best empirical cut-off value was achieved for a "three-feature combination" (size >3.3 cm, location below the superficial fascia and a P2 or P3 perfusion pattern) with sensitivity of 89%, specificity of 85% and a PPV and NPV of 86% and 88% respectively. In this context, the available specificity of MRI in the differentiation between malignant and benign soft-tissue masses ranges from 76% to 90% [5,31,32] and thus lies within the same diagnostic range. This means that the specificity of our proposed "three-feature combination" is at least comparable with the MRI results of Berquist et al [5] and Daniel et al [32], and is superior to the specificity defined by Moulton et al [31]; in this context, researchers must be mentioned who reported that MRI has low specificity in the differentiation between benign and malignant masses as most masses have a "rather" non-specific MR appearance [33].…”
Section: Discussionmentioning
confidence: 96%
“…The best empirical cut-off value was achieved for a "three-feature combination" (size >3.3 cm, location below the superficial fascia and a P2 or P3 perfusion pattern) with sensitivity of 89%, specificity of 85% and a PPV and NPV of 86% and 88% respectively. In this context, the available specificity of MRI in the differentiation between malignant and benign soft-tissue masses ranges from 76% to 90% [5,31,32] and thus lies within the same diagnostic range. This means that the specificity of our proposed "three-feature combination" is at least comparable with the MRI results of Berquist et al [5] and Daniel et al [32], and is superior to the specificity defined by Moulton et al [31]; in this context, researchers must be mentioned who reported that MRI has low specificity in the differentiation between benign and malignant masses as most masses have a "rather" non-specific MR appearance [33].…”
Section: Discussionmentioning
confidence: 96%
“…When patients have the tumor cell necrosis rate higher than 90% after chemotherapy, their 5-year survival rate will be up to 80%-90%. When patients have the tumor cell necrosis rate lower than 90%, their survival rate will be lower than 60% [4][5][6][7]. Hence, the postoperative chemotherapy scheme should be adjusted if the second condition occurs.…”
Section: Chemotherapymentioning
confidence: 99%
“…MR imaging is the most sensitive and accurate imaging technique for the evaluation of musculoskeletal tumors. 1,2 However, patients referred to the hospital for evaluation on suspicion of a bone or soft tissue malignancy frequently present to the orthopedic oncology clinic with MR images that also show typical features of nonmalignant or nonneoplastic entities. 3 The primary aim of imaging should be to reach a specific diagnosis (in the ideal case obviating the need for biopsy) or narrow the differential diagnosis, and to decide whether biopsy, surgical intervention, or simple observation are required for further management.…”
mentioning
confidence: 99%
“…There are also reports that MR imaging has low specificity in differentiation between benign and malignant masses, and most lesions demonstrate a nonspecific appearance. 2 Besides benign and malignant musculoskeletal tumors, there are numerous nontumoral entities that have similar morphologic and signal changes that can mimic imaging findings of musculoskeletal tumors. A large number of these lesions clearly have characteristic findings of nonneoplastic entities and do not need further workup.…”
mentioning
confidence: 99%